2020
DOI: 10.3390/ijerph17103634
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Physical Exercise Improves Pain Catastrophizing and Other Psychological and Physical Aspects in Women with Fibromyalgia: A Randomized Controlled Trial

Abstract: Fibromyalgia (FM) is a chronic syndrome characterized by widespread pain and other physical and psychological features. In this study, we aimed to analyze the effect of a low-intensity physical exercise (PE) program, combining endurance training and coordination, on psychological aspects (i.e., pain catastrophizing, anxiety, depression, stress), pain perception (i.e., pain acceptance, pressure pain threshold (PPT), and quality of life and physical conditioning (i.e., self-perceived functional capacity, enduran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 71 publications
4
73
1
15
Order By: Relevance
“…However, the mean value at the end of the treatment was higher than 8 points, considered the marked score for the diagnosis of psychological distress [ 45 ]. These results are similar to previous studies showing that aerobic exercise reduces pain intensity, mechanical pain sensitivity, and psychological distress [ 16 , 46 , 47 , 48 , 49 ], however, in this clinical trial, we achieved improvements with a TP without face-to-face sessions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the mean value at the end of the treatment was higher than 8 points, considered the marked score for the diagnosis of psychological distress [ 45 ]. These results are similar to previous studies showing that aerobic exercise reduces pain intensity, mechanical pain sensitivity, and psychological distress [ 16 , 46 , 47 , 48 , 49 ], however, in this clinical trial, we achieved improvements with a TP without face-to-face sessions.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies showed that individualized low-intensity aerobic exercise was well-tolerated by patients with FM [ 14 , 15 , 16 ]. These studies achieved positive effects on pain intensity, FM impact, hyperalgesia, physical function, catastrophizing, and psychological distress [ 14 , 15 , 16 ], without major adverse events [ 14 ]. In addition, aerobic exercise showed lower costs and larger positive effects compared to usual care [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to this, all patients presented high fatigue levels, severe sleep disturbances, and poor physical function. These baseline results are similar to those of previous studies that included patients with FMS [ 16 , 32 , 33 , 34 ]. Cardiorespiratory fitness and muscle strength are the central components of the physical requirements for work and daily life activities and are correlated with pain intensity and sleep disturbances.…”
Section: Discussionsupporting
confidence: 90%
“…Therapeutic exercise (TE) is one of the most investigated approaches for the management of FMS. Aerobic exercise, strengthening, and their combination have shown similar effects in improving fatigue, sleep disturbances, and physical function [ 12 , 13 , 14 , 15 , 16 ]. The effects of patient education have also been investigated in patients with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There have only been few reports on the effects of aerobic-resistance circuit training on pain. Circuit training has been reported to decrease postoperative pain after total knee arthroplasty 27 and pain perception in women with fibromyalgia 28 . Although these studies focused on postoperative pain and pain perception, the effect of aerobic-resistance circuit training for reducing CMP is still unknown.…”
Section: Introductionmentioning
confidence: 99%